Hey, diddle diddle - Eagle, Kin (Dallas, TX : Whispering Coyote Press, 1997)
This nonsense tale continues the story of the traditional rhyme in which the cow jumps over the moon.
Keywords: Cows-Fiction; Stories in rhyme